Suscetibilidade a movimentos de massa: um estudo geomorfológico na sub-bacia hidrográfica do rio Vacacaí Mirim a montante da barragem do DNOS, em Santa Maria/RS - Vargas, Luciani Vieira de (2015)
The objective of geo-morphological science is to study and understand diverse forms of surfaces in order to grasp the relation that is established between past and present of terrestrial surfaces with human beings, who are modifying agents of the environment. Regarding terrestrial surfaces, slopes are considered markers, even if they are not very steep, which are improper for human dwellings and use since they posit risk of natural mass movements. Thus, if such places are under anthropologic activities, either in terms of agriculture or for human dwellings, the process of mass movements can take place from slow to fast ones. Therefore, the present research consists in a study carried out in the sub-basin of Vacacaí Mirim River close to the DNOS dam with the objective of analyzing and understanding phenomena related to mass gravitational movements that took place in the observed area. Factors such as declivity, hypsometry, lithology and kinds of soil were mapped. According to the mapped data and field studies, episodes of surface movement like very slow landslides, rock dislodgments and bigger landslides were observed. From the patterns of mass movements of occurrences observed in the field, was diagnosed the western sector of the study area, as that was where most of the relief drive event during the study period. Based on the results it appears that the slope of the study area suffers considerable intensification in local (western sector) which occur use and human occupation, a fact that enhances the natural processes of gravitational mass movements.